Epidemiology of injuries in elite Women`s Artistic Gymnastics: a retrospective analysis of six seasons - Charpy, S.; Billard, P.; Dandrieux, P.-E.; Chapon, J.; Edouard, P. (BMJ Open Sport & Exercise Medicine, 2023)
Background Women`s Artistic Gymnastics (WAG) is a sport well known for requiring a heavy and difficult training load from a younger age to reach a high level of performance. This also is associated with an injury risk. Epidemiological studies are thus needed to improve injury prevention strategies.